Training in Interventional Pulmonology - Feller-Kopman, David; Yarmus, Lonny (Seminars in Respiratory and Critical Care Medicine, 2014)
The field of interventional pulmonology (IP) is a rapidly growing subspecialty of pulmonary and critical care medicine (PCCM), primarily focused on the evaluation and management of patients with lung nodules, masses, mediastinal and hilar adenopathy, central airway obstruction, and pleural disease. Traditionally passed on in the apprenticeship model, dedicated fellowships began in the early 2000s and there are currently approximately 24 IP fellowships throughout the United States. In addition to the evaluation and management of patients with the above diseases, the additional year provides training in advanced diagnostic and minimally invasive therapeutic procedures that are not specifically taught during a standard PCCM fellowship. This article will review the evolution of the field of IP as well as the pathways to learn advanced procedural techniques.
Keywords: interventional pulmonology; bronchoscopy; training; education